Religionens funktion i det danske fængselssystem i 1800-tallet - Bjørnsdatter Lindbock, Anna (Historisk Tidsskrift, 2013)
The Function of Religion in Danish Prisons in the 19th CenturyThe purpose of this article is to analyse and explain the function of religion in 19th Century Danish prisons. What part did religion play in the formation of ideology and practice of the prison? The starting point is two different interpretations of the historical issue aiming at a deeper understanding and broader coverage of the historical reality: Foucault described religion as one of the "means of power" used to re-educate the criminals, and it was his assumption that religion did not have an independent function. His analysis is important and should not be rejected simply because of its reductionist tendency. Peter Scharff Smith, who is inspired by Max Weber and Gauchet, interprets religion as a "code of values" and sees no contradiction in the meeting between Christianity and rationalism in the modern world. This leads him to the theory of "the technology of the self" which tries to involve the individual perspective in history. It is the assumption of this article, though, that the two interpretations do not adequately describe historical reality. Therefore, the article tries to contribute another historical aspect to broaden our understanding of the past. The article examines not only a "culture of modern ethnic Christianity" but also a "culture of believers" and its understanding of life and religious concepts. The method has involved the use of basic Christian definitions and identification with contemporary Christian "fundamentalism", based on the assumption that contemporary Christian "fundamentalism" is comparable to traditional Christianity of the 19th Century (fundamentalism understood as faith in the Bible and not military action). The idea is to achieve a deeper understanding of the roles of two Danish prison ministers based on sources related to their own views on their practices and starting points. The question of how representative the two ministers are, have not been answered in the article which must be seen as an attempt to explore new ground.